Genealogies of the secular: the making of modern German thought - Styfhals, Willem; Symons, Stéphane (SUNY Press, 2019)
Genealogy trouble: secularization and the levelling of theory / Kirk Wetters -- Modernity and its cryptotheologies: a Jewish perspective / Agata Bielik-Robson -- The "distance to revelation" and the difference between divine and worldly order: Walter Benjamin's critique of secularization as historical development / Sigrid Weigel -- Theology and politics: Ernst Cassirer and Martin Heidegger before, in and after the Davos debate / Jeffrey Andrew Barash -- Is progress a category of consolation? Kant, Blumenberg, and the politics of the moderns / Michaël Foessel -- Hannah Arendt, secularization theory, and the politics of secularism / Samuel Moyn -- Secularization and the symbols of democracy: Jacob Taubes's critique of Carl Schmitt / Martin Treml -- On the symbolic order of modern democracy / Jacob Taubes -- In Paul's mask: Jacob Taubes reads Walter Benjamin / Sigrid Weigel -- Secularization and theologization: introduction to Jan Assmann's monotheism / Daniel Steinmetz-Jenkins -- Monotheism / Jan Assmann.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geistesgeschichte 1900-2018; Säkularisierung; Deutschland; Säkularismus